1988
DOI: 10.1109/29.1644
|View full text |Cite
|
Sign up to set email alerts
|

Complete discrete 2-D Gabor transforms by neural networks for image analysis and compression

Abstract: Abstract-A three-layered neural network is described for transforming two-dimensional discrete signals into generalized nonorthogonal 2-D "Gabor" representations for image analysis, segmentation, and compression. These transforms are conjoint spatiahpectral representations [lo], [15], which provide a complete image description in terms of locally windowed 2-D spectral coordinates embedded within global 2-D spatial coordinates. Because intrinsic redundancies within images are extracted, the resulting image code… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
692
0
26

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,590 publications
(718 citation statements)
references
References 29 publications
0
692
0
26
Order By: Relevance
“…Preprocessing consists of the application of pseudo-polar coordinates (taking into account that the inner and outer circular boundaries may not be completely concentric) and standardizing the radial size of the iris (so that possible dilation of the pupil does not a ect the system) [19]. As for feature extraction, 2D Gabor wavelets [26] are used to perform a multiscale analysis of the iris [17,16,15]. A set of quadrature pair frequency-selective ÿlters are used to analyze regions of the image at di erent scales.…”
Section: Iris Identiÿcationmentioning
confidence: 99%
“…Preprocessing consists of the application of pseudo-polar coordinates (taking into account that the inner and outer circular boundaries may not be completely concentric) and standardizing the radial size of the iris (so that possible dilation of the pupil does not a ect the system) [19]. As for feature extraction, 2D Gabor wavelets [26] are used to perform a multiscale analysis of the iris [17,16,15]. A set of quadrature pair frequency-selective ÿlters are used to analyze regions of the image at di erent scales.…”
Section: Iris Identiÿcationmentioning
confidence: 99%
“…Specifically, it has been shown that Gabor filters model the spatial frequency and orientation responses of simple cells in the primary visual cortex [39,40]. The Gabor representation has been shown to be optimal in the sense of minimizing the joint two-dimensional uncertainty in space and frequency [41]. Since the Gabor filter bank is derived from a wavelet basis with dilations and orientations, they are essentially bandpass filters.…”
Section: B Methodsmentioning
confidence: 99%
“…structural [24], statistical [25][26][27] and random process [28], this work uses statistical measurements based on second order statistics [27]. These statistical descriptors have been estimated using the method of cooccurrence matrices applied to each region of an image.…”
Section: Texture Classificationmentioning
confidence: 99%